Eficácia de um programa aplicado por pais para ensino de nomeação de estados emocionais a crianças com Transtorno do Espectro Autista (TEA) - Libardi, Ana Luísa Polizel (2021)
Literature on naming emotional states indicates that people diagnosed with Autistic Spectrum Disorder (ASD) may have difficulty in developing such skills, and video procedures have been identified as effective for teaching this repertoire. The pandemic scenario of COVID-19 caused the suspension of in-person activities and, given the protective measures, such as social distancing, it was necessary to adopt a telehealth service (remote mode) for this research. The aim was to develop a parent-applied video program and investigate its effectiveness in teaching repertoires for naming emotional states from facial expressions to children with ASD. Three children with ASD, aged 3 to 6 years, and their parents participated in the study. The design used was a single subject A-B, and the procedure consisted of two experimental conditions: A) Baseline (probe) - control condition of variables, and B) Naming training - teaching condition. In Baseline (A) the summarized videos were applied (presentation only of the simulation situations in which the child-actress presented the emotions), and in the Naming Training (B) the full videos were applied (image presentation - frozen - with the face of the child-actress presenting the emotion at the beginning, with audio and the written word naming the emotional state, and followed by the simulation situation.The emotions trained were: 1) joy; 2) sadness and 3) fear. Data analysis assessed the relationship between children's responses to naming emotional states (dependent variable) in each naming training attempt applied by parents (independent variable). It was possible to develop the procedure, and the results showed that among the three participants, two learned (P1 and P3) to respond to the experimental task of naming the emotions of joy and sadness, and only P1 learned to name the emotion of fear. Keywords: Naming emotions; parente training; video; Autistic Spectrum Disorder.